The Effect of Influencer Endorsement, Online Customer Reviews, and Brand Image to Purchase Intention Mediated by Customer Trust in Online Shopping Activities on Tiktok - Permatasari, Harnung Indah; Wahyudi, Lilik (Journal of Organizational and Human Resource Development Strategies, 2024)
In shopping online, information plays a key role in decision-making. EWOM, Electronic word of mouth can be used as a reliable source of information. Consumer information is searched for by looking at customer reviews and influencer reviews. They represent various experiences and evaluations of a product that can be taken into consideration. Apart from these two things, Brand Image is also questionable whether it is still influential amidst the many EWOMs circulating. This study aims to examine the effect of influencer endorsements, online customer reviews, and brand image on purchase intentions mediated by trust. In this research, quantitative research was carried out and data were processed from 333 respondents from an online survey spread throughout Indonesia. SEM analyzed the collected data in SmatPLS. The results of the study show that online customer reviews and brand image have an effect on purchase intention and trust, but influencer endorsements do not.